Enhanced Reactivity of Aluminum Complexes Containing P-Bridged Biphenolate Ligands in Ring-Opening Polymerization Catalysis - Zou, Xue-Ru; Chang, Yu-Ning; Huang, Kuo-Wei; Liang, Lan-Chang (Frontiers in Chemistry, 2018)
Aluminum complexes containing [RP(O)(2-O-3,5-tBu2C6H2)2]2- (R = tBu (3a), Ph (3b)) have been synthesized, structurally characterized, and their reactivity studied in comparison with those of their [RP(2-O-3,5-tBu2C6H2)2]2- (R = tBu (2a), Ph (2b)) analogues. Treating AlMe3 with one equiv of H2[3a-b] in THF at 0 C affords quantitatively [3a-b]AlMe, subsequent reactions of which with benzyl alcohol in THF at 25 C generate [3a-b]Al(2-OCH2Ph)2. The methyl [3a-b]AlMe and the benzyloxide [3a-b]Al(2-OCH2Ph)2 are all active for catalytic ring-opening polymerization (ROP) of -caprolactone and rac-lactide (rac-LA). Controlled experiments reveal that [3a]Al(2-OCH2Ph)2 is competent in living polymerization. Kinetic studies indicate that [3a]AlMe, in the presence of benzyl alcohol, catalyzes ROP of rac-LA at a rate faster than [3b]AlMe and [2a]AlMe(THF) by a factor of 1.8 and 23.6, respectively, highlighting the profound reactivity enhancement in ROP catalysis by varying the P-substituents of these biphenolate complexes of aluminum.